Experimental investigations in chiselling solid concrete - Peldschus, Friedel; Wild, Jens-Thorsten (Journal of Civil Engineering and Management, 2003)
Experimental research was performed for analysing the chiselling process. The conditions of crack formation and crack propagation have been analysed. In the first step impact tests with a standard chisel shapes and with a pointed chisel were performed. These tests represented the basic investigations into the chisel load effects on mechanical processing of concrete. In the next step precise modifications were applied to the flat-chisel cutting edge with the aim of improving the cutting-edge geometry.First Published Online: 26 Jul 2012